Transnational patents: Structures, trends and recent developments - Rainer Frietsch; Taehyun Jung (Expertenkommission Forschung und Innovation (EFI), 2009)
In this study, we compared the profile of German Transnational Patents with the patenting profiles of other countries from several different angles. Germany is a stronghold in international patenting in terms of the absolute number of filings (ranked the third only after the United States and Japan) and the number of filings per employee (ranked the fourth after Swiss, Sweden, and Finland). However, its growth rate is lower than the top-patenting countries and even below the EU average. This indicates that comparative technological advantage of Germany may be debilitated in the future. In order to revamp technological advantage of Germany, tracking the situation of fast-growing countries such as Korea and China would help. Probably more serious problem for German innovative capabilities is its weakness in fast-growing, technology-intensive industries such as ICT and biopharmaceuticals. While Germany is very strong in patenting in moderately technology-intensive sectors such as machinery and automobile, its technological presence in terms of international patent filings are very weak in Electronics, ICT, and biopharmaceuticals. Moreover, patent filings from small and medium-sized enterprises in these sectors are much weaker. As a remedy to this problem, international collaboration can be a candidate solution. We showed that international co-invention occurs more frequently in the weaker technology areas. This indirectly indicates that international collaboration would help a country to strengthen its currently weak technological capability. International co-invention has been growing faster than the growth of patenting. Also, in rapidly-growing fields such as chemistry and electronics, international co-invention is more frequently observed. Therefore, policy instruments that can promote international research collaboration and attract multinational companies in these growing fields to build their research centres in Germany would help Germany advance into a major technology player in these fields. In addition, to bolster technological capabilities of small and medium-sized enterprises in these growing, technology-intensive sectors, promoting interorganizational technology transfer, especially from universities, and institutionalizing venture capital would be essential.
Keywords: 330; Patent; Erfindung; Wissenstransfer; KMU; International; Deutschland